Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

dnance

  • 3 years ago

Write the equation y - 2 = 2(x - 3) in standard form.

  • This Question is Closed
  1. jazy
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Change into Slope-Intercept form. y = mx + b y - 2 = 2(x - 3) Distribute. y - 2 = 2x - 6 Add 2. y = 2x - 4 NOW change to standard form. Ax + By = C y = 2x - 4 Subtract 2x. -2x + y = -4 A can NOT be a negative. Multiply everything by -1. 2x - y = 4 <---Standard form

  2. dnance
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thank you

  3. jazy
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    welcome. (:

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy